Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1472-6963-11-278
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of three populational screening strategies for cervical cancer in the county of Valles Occidental: CRICERVA clinical trial

Abstract: BackgroundA high percentage of cervical cancer cases have not undergone cytological tests within 10 years prior to diagnosis. Different population interventions could improve coverage in the public system, although costs will also increase. The aim of this study was to compare the effectiveness and the costs of three types of population interventions to increase the number of female participants in the screening programmes for cancer of the cervix carried out by Primary Care in four basic health care areas.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…A recent evaluation of this strategy [ 29 ] showed that underscreened women had a high burden of cervical disease. Attempts to extend these initiatives into an organized activity are undergoing [ 30 ] a randomized trial inviting these women to participate in the screening program.…”
Section: Discussionmentioning
confidence: 99%
“…A recent evaluation of this strategy [ 29 ] showed that underscreened women had a high burden of cervical disease. Attempts to extend these initiatives into an organized activity are undergoing [ 30 ] a randomized trial inviting these women to participate in the screening program.…”
Section: Discussionmentioning
confidence: 99%
“…This baseline higher screening coverage among the youngest is likely to be explained by the higher contact with reproductive health care centers and implying that women are more likely to be offered a screening test together with other medical services related to contraception or reproduction. Although our control arm showed poorer screening uptake compared to the IGs (84.1%) the final coverage was higher (64.8%) than the average reported for Catalonia [16]. This can be explained by the fact that the four areas included in the study from SAP Cerdanyola have traditionally shown to have a good connection with the NHS.…”
Section: Discussionmentioning
confidence: 58%
“…This can be explained by the fact that the four areas included in the study from SAP Cerdanyola have traditionally shown to have a good connection with the NHS. These areas are represent a metropolitan urban environment with high predominance of working class, where half of the women have a primary school completed or less and show an almost universal use of the Public Health Services compared to other areas in Catalonia [16]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study is to perform a cost-effectiveness analysis alongside the CRICERVA clinical trial, (Acera et al: Increasing cervical cancer screening coverage: a randomised, community-based clinical trial, accepted and forthcoming) of three different active interventions to promote the uptake of screening for cervical cancer in general practice. An orientative protocol of this economic evaluation was first published in 2011 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%